Long-Duration Response to Levodopa in Patients with Early Parkinson’s Disease: Pharmacodynamics, Neuroplasticity, and Clinical Implications - Giorgia Sciacca (Biomedicines, 2026)
Background: The most effective pharmacological treatment for Parkinson’s disease (PD) remains levodopa, whose responsiveness is distinguished into two temporally and mechanistically distinct components: the short-duration response (SDR), which lasts hours, closely paralleling drug plasma concentration, and the long-duration response (LDR), which derives from prolonged administration of levodopa and persists for days to weeks after drug discontinuation. The mechanisms underlying the LDR and, in particular, the behavior in early PD patients are incompletely understood. This review aims to gather current evidence on the pharmacodynamics, neurobiological substrate, natural history, and clinical implications of the LDR, with a specific focus on early PD patients. Methods: A narrative review was conducted based on a selection of original research articles, clinical studies, and reviews identified through PubMed/MEDLINE, covering the period from January 1995 to July 2026. Studies were selected for their methodological relevance to the characterization of LDR in drug-naive or early-stage PD patients, including pharmacodynamic studies, neuroimaging investigations, and neurophysiological assessments. Results: Evidence consistently demonstrates that the LDR is a pharmacodynamically distinct component of levodopa response, present from the earliest stages of dopaminergic therapy. In drug-naive patients, the LDR represents a quantitatively substantial fraction of total levodopa benefit, and it is linked to modifications in cortical excitability, dopaminergic neuroplasticity, and motor learning. Structural neuroimaging identifies predisposing gray matter features in motor cortex regions. Whether LDR magnitude declines with disease and treatment duration, and thereby underlies the emergence of motor fluctuations, remains disputed across studies. This discrepancy appears attributable, at least in part, to differences in how the LDR is measured (direct washout assessment versus inference against a projected untreated trajectory) rather than necessarily to divergent underlying biology. Conclusions: The LDR to levodopa represents a neurobiologically and clinically significant dimension of levodopa response. Its characterization in early PD patients may refine therapeutic strategies, inform the design of neuroprotection trials, and open new possibilities for precision medicine approaches.